Factors affecting metabolic and electrolyte changes after reperfusion in liver transplantation - Tsinari, K. K.; Misiakos, E. P.; Lawand, C. T.; Chatzipetrou, M. A.; Lampadariou, K.; Neto, A. B.; Llanos, J. C.; Tamura, S.; Gyamfi, A. R.; Tzakis, A. G. (Elsevier B.V., 2004)
Background. The metabolic and electrolyte changes were evaluated after various durations of cold and warm ischemia times to correlate ASA status with hemodynamic changes that may affect the severity of the reperfusion syndrome.Patients and methods. Sixty-one patients who underwent liver transplantation (OLT) were monitored by arterial pH, PaO2, PaCO2, HCO3, BE, K+, Ca2+, Na+, GL, and serial Ht at three specific times: after the skin incision (baseline), 10 minutes before reperfusion (T-2), and 10 minutes after reperfusion (T-3). Changes in metabolic parameters were correlated with ASA status, hemodynamic changes, time of OLT, as well as cold and warm ischemia times.Results. The pH in ASA IV patients was significantly lower at T-1 and T-3, and PCO2 higher in ASA V at T-1. A significant correlation was observed between pH, PaCO2, HCO3 BE, Na+, Ca2+, and glucose with the phase of the procedure. The pH and HCO3 decreased significantly from T-1 and T-2, increasing during T-3. Ca2+ fell from T-1 to T-2 increasing in T-3. Mean glucose and sodium levels increase from T-1 to T-3. Mean BE dropped from T-1 to T-2 and increased at T-3 without a significant correlation between the metabolic parameters in any phase of the study and the cold or warm ischemia times. Patients with a high ASA status showed an increased risk for cardiovascular collapse after reperfusion.Conclusions. Patients with advanced ASA status are more prone to metabolic and acid-base disturbances during reperfusion, without any relation to the cold or warm ischemia times. High ASA status shows an increased risk for cardiovascular collapse after reperfusion.